Steady and transient operation of an organic Rankine cycle power system. (April 2019) - Cao, Shuang; Xu, Jinliang; Miao, Zheng; Liu, Xiulong; Zhang, Ming; Xie, Xuewang; Li, Zhi; Zhao, Xiaoli; Tang, Guihua
Abstract: The Organic Rankine Cycle (ORC) driven by low-grade energy can operate in off-grid mode. Here, we report the steady and transient characteristics of an ORC system. A single screw expander and a synchronous generator convert mechanical power to electricity. A lamp array simulates the variable external loads. The quality parameters including electric frequency, electric power and effective voltage are measured by a power meter. We show that at setting frequency of 50 Hz, the maximum system efficiency can be reached when the external load is not larger than the ORC power capacity. The expander isentropic efficiency is above 80% for the vapor superheating of 5–10 K at expander inlet. A control strategy is proposed to achieve better system performance under varied heat source and environment conditions. By use of residual frequency and adjusting pumping frequency, the vapor pressure at expander inlet can be automatically adjusted to reach the optimal value. Transient tests indicate that the electric quality is insensitive to the step change of external loads and heat/cold sources parameters. The thermohydraulic parameters are self-adapted to the change of external parameters. This work provides a self-adapting strategy for ORC operation at varied heat/cold source parameters. Highlights: The steady and transient operation characteristics of an ORC system are investigated. A single screw expander and a synchronous generator are included in the system. The electric frequency of 50 Hz is reached if external load is not larger than ORC capacity. Electric energy quality parameters are insensitive to the step change of external parameters.